The Role of Adipose Tissue and Adipokines in Obesity-Related Inflammatory Diseases - Carmela Rita Balistreri; Calogero Caruso; Giuseppina Candore (Mediators of Inflammation)
Obesity is an energy-rich condition associated with overnutrition, which impairs systemic metabolic homeostasis and elicits stress. It also activates an inflammatory process in metabolically active sites, such as white adipose tissue, liver, and immune cells. As consequence, increased circulating levels of proinflammatory cytokines, hormone-like molecules, and other inflammatory markers are induced. This determines a chronic active inflammatory condition, associated with the development of the obesity-related inflammatory diseases. This paper describes the role of adipose tissue and the biological effects of many adipokines in these diseases.